THE INFLUENCE OF DISTINCT TYPES OF MEDIA INTERACTION AND GENDER ON THE PRODUCTIVITY OF UNIVERSITY STUDENTS AS MEASURED BY THE NUMBER OF MEANINGFUL WORDS - Winarto, Agustinus Rudi (IJIET (International Journal of Indonesian Education and Teaching), 2023)
This analysis seeks to discover how the richness of meaningful words is affected by the diversity of media and gender. The two separated forms of media in computer-mediated communication, which are real names (CMR) and anonym (CMA), are connected to the production of meaningful interaction in problem-solving exchanges among pupils. Furthermore, computer-based communication has added a layer of invisibility which has caused an increase in daring word usage in conversations using computers. To assess this issue, the research will look into criminal puzzles discussed in clubs, to determine if there is any impact from the various types of media and gender variation. The research used empirical analysis methods to review the effect of different media and sex on the number of meaningful words produced by 30 participants, 20 female and 10 male. Through analysis of conversations in the conversation room, a two-way ANOVA test was administered to figure out the impact of media and gender on the number of meaningful words. The investigation presented that there was no meaningful impact of media diversity and gender on the number of words produced by students in the investigation. The data suggested that any changes in media or gender had no notable effect on productivity.